Pacific islands' bilateral trade: The role of remoteness and of transport costs - Lisa Borgatti (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Bilateral trade of geographically distant countries is likely to be negatively affected by the distance separating them from their trading partners and positively affected by their remoteness, defined as the average weighted distance between two countries with weights reflecting the absorptive capacity of the partner country. In presence of competitive transport costs, the effect of remoteness and distance is diluted. An augmented gravity model applied to the Pacific islands' bilateral trade from 1980 to 2004 shows that a doubling of the elasticity of distance would decrease their average bilateral trade by 80 per cent. Remoteness positively affects the Pacific islands' bilateral trade, but does not compensate for the negative effect of distance. The opposite is found for the Caribbean islands, where the elasticity of trade with respect to remoteness is eight times bigger than that for the Pacific islands. By lowering transport costs, improved infrastructure fosters trade. A K-means cluster analysis for 30 small island developing states shows that the Pacific islands belong to the clusters with the weaker infrastructure stocks, leaving them with a large scope for improvement.
Keywords: C23; C24; F14; O56; O57; R49; 330; bilateral trade; remoteness; transport costs; infrastructure; gravity model; Pacific islands; Internationale Wirtschaftsbeziehungen; Entfernung; Transportkosten; Gravitationsmodell; Insel; Pazifischer Raum